2014
DOI: 10.1073/pnas.1322559111
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic girdle and fin ofTiktaalik roseae

Abstract: A major challenge in understanding the origin of terrestrial vertebrates has been knowledge of the pelvis and hind appendage of their closest fish relatives. The pelvic girdle and appendage of tetrapods is dramatically larger and more robust than that of fish and contains a number of structures that provide greater musculoskeletal support for posture and locomotion. The discovery of pelvic material of the finned elpistostegalian, Tiktaalik roseae, bridges some of these differences. Multiple isolated pelves hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 21 publications
4
71
0
1
Order By: Relevance
“…Our discovery that the evolution of larger eye sockets occurred in animals that were primarily aquatic is in line with other critical conclusions of the past several decades of early tetrapod paleontology, which has found that robust limbs evolved in primarily aquatic animals (9,10) and that fingers and toes evolved in primarily aquatic animals (11). Notably, the increase in eye size starting in the elpistostegalians coincided with a distinct change in the placement of eyes in this group.…”
Section: Significancesupporting
confidence: 89%
“…Our discovery that the evolution of larger eye sockets occurred in animals that were primarily aquatic is in line with other critical conclusions of the past several decades of early tetrapod paleontology, which has found that robust limbs evolved in primarily aquatic animals (9,10) and that fingers and toes evolved in primarily aquatic animals (11). Notably, the increase in eye size starting in the elpistostegalians coincided with a distinct change in the placement of eyes in this group.…”
Section: Significancesupporting
confidence: 89%
“…Panderichthys, Tiktaalik, Elpistostege), there seems to be an evolutionary trend towards the loss of median fins other than the caudal fin Shubin, Daeschler, & Jenkins, 2014). (Furlong & Holland, 2002;Janvier, 2008;Ota, Fujimoto, Oisi, & Kuratani, 2013;Shimeld & Donoghue, 2012).…”
Section: The Dipnomorpha Include the Porolepiformes And Thementioning
confidence: 99%
“…Proximal elements of the wrist (ulnare and intermedium) and ankle (fibulare and intermedium) are present in the more fish-like tetrapodomorphs (Andrews and Westoll 1970;Boisvert et al 2008; Davis et al 2004; Shubin et al 2006) predating the appearance of tetrapod digits. A single element in the tarsus of Tiktaalik is a possible intermedium (Shubin et al 2014). Only a single ossified bone identified as the intermedium is known for the carpus of the stem tetrapod Acanthostega (Coates 1996), but a second stem tetrapod Tulerpeton has an ossified ulnare and intermedium (Lebedev and Coates 1995).…”
Section: Introductionmentioning
confidence: 99%